EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH MELALUI TPS 3R GIRI MULYA DI DESA GIRIREJO KABUPATEN MAGELANG - Uswatun Hasanah; Dewi Erowati (Journal of Politic and Government Studies, 2026)
Waste management is an environmental issue that requires effective public policy at the local level. Girirejo Village, Ngablak District, Magelang Regency implements a waste management policy through the Reduce, Reuse, Recycle Waste Processing Facility (TPS 3R) Giri Mulya as a community-based initiative. This study aims to evaluate the implementation of this policy and analyze the distribution of its benefits among the actors involved. This research uses a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving the village government, TPS 3R managers, and community members as service users. The analysis applies William N. Dunn’s policy evaluation indicators, including effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the waste management policy through TPS 3R Giri Mulya has been implemented but has not yet achieved optimal results. The policy strengthens village waste management institutions and improves environmental cleanliness in areas that receive services. However, communities in hamlets that are not yet covered by waste collection services have not fully experienced these benefits due to limited service coverage and operational capacity. These findings show that although the policy generates environmental and institutional benefits, the distribution of benefits across actors and areas remains uneven.